What is a Psychological Task? The Operational Pliability of “Task” in Psychological Laboratory Experimentation - Morrison, Hazel; McBriar, Shannon; Powell, Hilary; Proudfoot, Jesse; Stanley, Steven; Fitzgerald, Des; Callard, Felicity (Engaging science, technology, and society, 2019)
There has been no sustained sociological analysis of a near ubiquitous feature of psychological laboratory experimentation: the task. Yet the task is central in arranging the means by which phenomena are isolated and brought into the experimental scientist’s purview. As scientific objects, states such as mind wandering and daydreaming have been made visible in experiments that draw on a (sometimes) sharp distinction between what it means to be either “on task” or “off task”––which entails a long history of what it means to have a subject attend to her task, a central aspect of the psychology experiment since its foundation. Through an analysis of qualitative interviews with research participants in studies of so-called “mind wandering,” it becomes clear that task is deployed and understood in multiple ways: it is often hard to distinguish when a person is on task and when they are not; when participants reflect on their own internal states the boundedness that the concept relies upon is drawn sharply into question; and the complex spatio-temporal organization of experiences of both mind wandering and task disrupts the metaphorical structures that the scientific literature has baked into these terms. The term “operational pliability” allows us to understand how the pliability of the practice and concept of task is central to how task functions. Operational pliability offers a way of understanding how particular elements in scientific investigation are easily adaptable and at the same time are able to hold some kind of shape or form.